Isotope shift in the electron affinity of lithium - Bubin, Sergiy; Komasa, Jacek; Stanke, Monika; Adamowicz, Ludwik (American Institute of Physics Publishing, 2009)
Very accurate electron affinity EA calculations of 6Li and 7Li and Li have been performed using explicitly correlated Gaussian functions and a variational approach that explicitly includes the nuclear motion in the calculations i.e., the approach that does not assume the Born–Oppenheimer approximation . The leading relativistic and quantum electrodynamics corrections to the electron affinities were also calculated. The results are the most accurate theoretical values obtained for the studied systems to date. Our best estimates of the 7Li and 6Li EAs are 4984.9842 30 and 4984.9015 30 cm−1, respectively, and of the 7Li/ 6Li EA isotope shift is 0.0827 cm−1
Keywords: physics; electron affinity of lithium